Die Larynxmaske – Schritt für Schritt - Dembinski, Rolf; Scholtyschik, Daniel (DMW - Deutsche Medizinische Wochenschrift, 2019)
Laryngeal masks are supraglottic airway devices developed in the early 1980s. Today, they are frequently used in clinical routine to provide airway access for mechanical ventilation in patients undergoing surgery with a short duration. Moreover, the they have also become integral part of difficult airway management in patients who cannot be intubated by the use of conventional laryngoscopy.Relevant advances have been made to simplify their positioning and improve tightness with the aim to allow for the use of higher airway pressures during mechanical ventilation thereby reducing the risk of gastric insufflation and pulmonary aspiration. Focusing on this goal, several different prototypes have been developed and introduced in clinical practice until today. However, even these new developed laryngeal masks still do not provide reliable protection against pulmonary aspiration until today. Consequently, their use In critical care medicine is still limited to rescue situations with intubation failure.In this review some of the most popular lanryngeal masks are presented, indications for their use are outlined and their handling is described.
Keywords: Maschinelle Beatmung; Atemwegsmanagement; supraglottische Atemhilfe; Aspiration